Oxygen-releasing seed coating enhances yield and resource use efficiency in direct-seeded rice - Shi, Yuanqing; Yin, Huilai; Zhu, Yuemei; Liu, Ruhongji; Chen, Qiqi; Xie, Hongkun; Liu, Binbin; Cheng, Qingyue; Shu, Chuanhai; Liu, Ning; Ma, Jun; Sun, Yongjian; et al. (Frontiers in Plant Science, 2026)
To address seed decay in direct-seeded rice caused by waterlogging resulting from inadequate field leveling, this study conducted split-split-plot field experiments in Chongzhou City, Sichuan Province (103°38’31’’–103°39’22’’ E, 30°33’16’’–30°33’54’’ N). Specifically, two hybrid rice varieties previously identified as flood-resistant (V1: Jinyou 1319) and flood-sensitive (V2: Jingliangyou 1377) were assigned to the main plots, wet direct seeding (P1) and water direct seeding (P2) were compared in the subplots, and the coating (C1) and no-coating (C2) treatments were applied to the sub-subplots. In the coating treatment with water direct seeding, the seedling percentage of V1 and V2 increased by 25.58% and 78.54%, respectively, the number of effective panicles increased by 4.69% and 12.95%, respectively, and the seed setting rate improved by 15.05% and 16.64%, respectively. This synergy boosted the yields of the two varieties by 23.15% and 31.77%. In particular, the yield of V2 with water direct seeding with coating matched that under wet direct seeding without coating. With little difference in total energy consumption (≤ 1.88%), the sensitive variety with water direct seeding and coating saved irrigation water and labor inputs by 13% and 17%, respectively, in the demonstration area (calculated based on the input of the demonstration area). With water direct seeding, the stable oxygen supply from the coating improved the seed germination rate and seedling growth vitality, especially for the sensitive variety. Thus, the oxygen-releasing coating achieved yield increases, resource conservation, and efficiency enhancement synergistically, providing a valuable solution for the development of direct-seeded rice in China’s hilly regions.